Java 2 Web developer certification study guide - Levi, Natalie (Sybex, 2003)
The Java web developer certification is the next logical step for anyone interested in moving into the world of Enterprise Java. This Study Guide provides: In-depth coverage of every exam objective. Practical information on programming servlets, developing JSP pages, and using custom tags. Hundreds of challenging review questions, in the book and on the CD. Leading-edge exam preparation software, including a testing engine